Giant Volume Change and Topological Gaps in Temperature‐ and Pressure‐Induced Phase Transitions: Experimental and Computational Study of ThMo2O8. Issue 3 (2nd December 2015) - Xiao, Bin; Kegler, Philip; Gesing, Thorsten M.; Robben, Lars; Blanca‐Romero, Ariadna; Kowalski, Piotr M.; Li, Yan; Klepov, Vladislav; Bosbach, Dirk; Alekseev, Evgeny V.
Abstract: By applying high temperature (1270 K) and high pressure (3.5 GPa), significant changes occur in the structural volume and crystal topology of ThMo2 O8, allowing the formation of an unexpected new ThMo2 O8 polymorph (high‐temperature/high‐pressure (HT/HP) orthorhombic ThMo2 O8 ). Compared with the other three ThMo2 O8 polymorphs prepared at the ambient pressure (monoclinic, orthorhombic, and hexagonal phases), the molar volume for the quenched HT/HP–orthorhombic ThMo2 O8 is decreased by almost 20 %. As a result of such a dramatic structural transformation, a permanent high‐pressure quenchable state is able to be sustained when the pressure is released. The crystal structures of the three ambient ThMo2 O8 phases are based on three‐dimensional (3D) frameworks constructed from corner‐sharing ThO x ( x= 6, 8, or 9) polyhedra and MoO4 tetrahedra. The HT/HP–orthorhombic ThMo2 O8, however, crystallizes in a novel structural topology, exhibiting very dense arrangements of ThO11 and MoO4+1 polyhedra connecting along the crystallographic c axis. The phase transitions among all four of these ThMo2 O8 polymorphs are unveiled and fully characterized with regard to the structural transformation, thermal stability, and vibrational properties. The complementary first principles calculations of Gibbs free energies reveal the underlying energetics of the phase transition, which support the experimental findings. Abstract : Under pressure : The study of ThMo2 O8 under high‐temperature/high‐pressure conditions at 3.5 GPa reveals a large 20 % volume change accompanied by significant structural contraction along the c axis. Owing to such a high density increase following by structural recombination, the high‐temperature/high‐pressure polymorph is kinetically stable at ambient conditions.